Лингвистический портрет слова „чиновник” - Frołowa, Olga (Studia Rossica Posnaniensia, 2010)
The article deals with the semantics and usage of the word chinovnic (official). The author views “the behavior” of this noun in the Russian texts of 18th–19th and 20th, 21st c. The investigation is based on the materials of Russian National Corpus (ruscorpora.ru). In the texts of 18th–19th c. the noun is used in a model “noun + proper name”, but in the modern use this model is lost, the noun chinovnic draws closer to the noun bureaucrat (pedant). In the article the main and peripheral senses of the noun chinownis are described: hired labor, disinterested attitude, lack of individuality. Native speakers of modern Russian avoid too negative descriptions contained in the word bureaucrat, which are perceived as too negative and prefer to use ambiguous noun such as chinovnic.